High-performance polyketone copolymer containing phthalazinone structure and synthesis method thereof

The existing polyketone copolymer is solved by polymerizing 2-benzimidazolinone and diazepanone biphenol with benzene ring-containing dihalogen monomers, thereby increasing the nitrogen content in the polyketone copolymer. The problem of insufficient glass transition temperature has achieved heat resistance and widespread application in high-temperature environments.

CN119390978APending Publication Date: 2025-02-07ORION NEW MATERIALS (SHANDONG) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510000781.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The glass transition temperature of existing polyketone copolymers is insufficient, limiting their application in high temperature environments.

Method used

2-benzimidazolinone and diazepinone biphenol are used as polymerization monomers, and the nitrogen content is increased by polymerization reaction with the dihalogen monomer containing benzene ring, thereby improving the glass transformation of polyketone copolymers. Transfer temperature.

Benefits of technology

The glass transition temperature of polyketone copolymer is significantly improved to reach above 253°C, enhancing its heat resistance stability and service life in high temperature environments, while improving its dissolution performance and expanding application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390978A_ABST
    Figure CN119390978A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance polyketone copolymer containing a phthalazinone structure and a synthesis method thereof, and belongs to the technical field of polyketone copolymer synthesis, and the preparation method comprises the following steps: (1) in an inert atmosphere and in the presence of a catalyst, carrying out a polymerization reaction on 2-benzimidazolone, phthalazinone diphenol and a dihalogenated monomer containing a benzene ring in an organic solvent to obtain a polymerization product; a polymer precursor is obtained; (2) purifying and treating the polymer precursor prepared in the step (1) to obtain a polyketone copolymer; the ratio of the total amount of substance of the 2-benzimidazolone and the phthalazinone diphenol to the amount of substance of the dihalogenated monomer containing the benzene ring is (1-1.06): (1-1.06), and the ratio of the amount of substance of the phthalazinone diphenol to the amount of substance of the 2-benzimidazolone is (0.01-0.99): (0.01-0.99). The phthalazinone diphenol and the 2-benzimidazolone provide carbon-nitrogen bonds for the polyketone copolymer, the thermal stability of the material is improved, meanwhile, the non-coplanar structure of the phthalazinone diphenol makes up the problem that the solubility of the material is reduced due to increase of the carbon-nitrogen bonds, and the solubility of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polyketone copolymer synthesis, and in particular to a high-performance polyketone copolymer containing a phthalazinone structure and a synthesis method thereof. Background Art

[0002] Polyketone copolymers are a type of special engineering material with excellent properties. They have high thermal stability, dimensional stability, good processing performance and electrical properties. They are widely used in aerospace, automotive industry, electronics and electrical, and medical machinery.

[0003] The glass transition temperature of the polyketone copolymer in the prior art is not enough to meet its application at high temperature. Chinese patent CN103450478B discloses a polyketone homopolymer synthesized with 2H-benzimidazol-2-one and 4,4'-difluorobenzophenone as monomers, and the glass transition temperature is 226°C. U.S. Patent US8609801B2 discloses a new type of polymer containing 2H-benzimidazol-2-one groups. The glass transition temperature of the polyketone copolymer composed of 2H-benzimidazol-2-one, 2,2-bis(4-hydroxyphenyl)propane and 4,4'-difluorobenzophenone is 170°C-200°C, and the glass transition temperature of the polyketone copolymer composed of 2H-benzimidazol-2-one, 4,4'-bisphenol and 4,4'-difluorobenzophenone is 217°C-235°C.

[0004] Since the glass transition temperature of the above polyketone copolymers is relatively low, their application will be limited in environments above 255°C. For example, in the injection molding process of electronic devices, the polymer needs to be able to maintain its shape at a temperature of 240°C. Therefore, special engineering plastics with higher heat and temperature resistance need to be further developed.

[0005] In view of the above problems in the prior art, the present invention combines many years of design and use experience in related fields to design a high-performance polyketone copolymer containing a diazinone structure and a synthesis method thereof to overcome the above defects. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a high-performance polyketone copolymer containing a diazinone structure and a synthesis method thereof, in which 2-benzimidazolidinone and diazinone diphenol are reacted together as polymerization monomers to increase the nitrogen content and increase the glass transition temperature to above 253°C. The copolymer can be used in high-temperature environments for a long time and has a long service life. At the same time, the solubility performance of the polyketone copolymer is increased, thereby increasing the application scenarios.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: a method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure, comprising the following steps: (1) In an inert atmosphere and in the presence of a catalyst, 2-benzimidazolone, phthalazinone biphenol and a dihalogenated monomer containing a benzene ring are polymerized in an organic solvent to obtain a polymer precursor; (2) The polymer precursor obtained in step (1) is purified and then treated to obtain a polyketone copolymer; The total amount of the phthalazinone biphenol and 2-benzimidazolinone and the amount of the dihalogenated monomer containing a benzene ring is 1-1.06:1-1.06, and the amount of the phthalazinone biphenol and 2-benzimidazolinone is 0.01-0.99:0.01-0.99; In step (1), the total amount of phthalazinone biphenol and 2-benzimidazolidinone to the amount of catalyst is 1:1.04-1.12.

[0008] Preferably, the dihalogenated monomer containing a benzene ring is Formula I, and / or Formula II; Wherein, Y is chlorine or fluorine, X is chlorine or fluorine, and Y and X are the same or different.

[0009] Preferably, when the dihalogenated monomer containing a benzene ring in step (1) is a monomer containing a structure of formula I and a monomer containing a structure of formula II, the molar ratio of the monomer containing a structure of formula I to the monomer containing a structure of formula II is 7-60:40-93.

[0010] Preferably, the molar ratio of the monomer containing the structure of formula I to the monomer containing the structure of formula II is 15:85.

[0011] Preferably, when the dihalogenated monomer containing a benzene ring is a monomer containing a structure of formula II, the molar ratio of the diazonone biphenol to 2-benzimidazolidinone is 0.05-0.6:0.4-0.95.

[0012] Preferably, in step (1), the catalyst is selected from anhydrous sodium carbonate or anhydrous potassium carbonate, and the organic solvent is selected from any one of diphenyl sulfone, isopropylbenzene hydroperoxide, N,N-dimethylformamide, cyclopentane, and N-cyclohexylpyrrolidone, or a combination of several thereof.

[0013] Preferably, the preparation of the polymer precursor in step (1) comprises the following steps: S1: at 140-200°C, 2-benzimidazolidinone and phthalazinone-biphenol react with a catalyst to generate salts respectively, the reaction time is 1-2h, and the reaction system is dehydrated to a water content of ≤1000ppm; S2: raising the temperature to 180-280° C., and performing a prepolymerization reaction between the salt and the dihalogenated monomer containing a benzene ring to obtain a prepolymer, and the reaction time is 0.5-6 hours; S3: polymerizing the prepolymer in step S2 to obtain a polymer precursor at 220-320°C, with a reaction time of 2-8h; Step S3 adopts gradient heating, and the heating rate is 1-5°C / min.

[0014] Preferably, when the dihalogenated monomer containing a benzene ring is a monomer containing a structure of formula I and a monomer containing a structure of formula II, the prepolymer in step S3 is reacted at 280°C for 2h, then heated to 300°C for 2h, and finally reacted at 320°C for 4h, with a heating rate of 1°C / min.

[0015] Preferably, the post-purification treatment in step (2) comprises the following steps: T1: adding the mixture after the reaction in step S3 into a dispersant and dispersing it so that the polymer particles are ≤1 mm; T2: at 60-100° C., the dispersed material in step T1 is washed several times with a 3%-50% by mass phosphoric acid aqueous solution and pure water, and then dried.

[0016] The present invention also provides a high-performance polyketone copolymer containing a phthalazinone structure obtained by the above-mentioned synthesis method, wherein the polyketone copolymer comprises repeating units shown in Formula 1 and Formula 2: The formula 1 is , and / or, ; The formula 2 is , and / or, ; The total number of repeating units shown in Formula 1 is a, and the total number of repeating units shown in Formula 2 is b, wherein a and b are both positive integers, 1≤a≤5000, 1≤b≤5000.

[0017] The invention is beneficial in that: 1. In the present invention, both 2-benzimidazolidinone and phthalazinone biphenol can be used as nucleophilic monomers to polymerize with dihalogenated monomers containing benzene rings. The two have small steric hindrance and fast reaction rate. 2-benzimidazolidinone and phthalazinone biphenol are synergistic. On the one hand, both 2-benzimidazolidinone and phthalazinone biphenol can increase the N element content in the polymer, provide carbon-nitrogen bonds for the polyketone copolymer, and make the polyketone copolymer have a higher glass transition temperature and heat stability, and its glass transition temperature is ≥253°C. On the other hand, phthalazinone biphenol has a non-coplanar structure, which can avoid the polyketone copolymer from forming a stretched and straight linear configuration, increase the solubility of the polyketone copolymer, alleviate the problem of reduced solubility caused by the increase of carbon-nitrogen bonds and the increase of polymer structural rigidity, increase the processability of the polyketone copolymer, and thus increase the application scenarios.

[0018] 2. The present invention uses 2-benzimidazolidinone and phthalazinone biphenol as nucleophilic monomers, and respectively carries out dehydration condensation with monomers containing a structure of formula I and a monomer containing a structure of formula II. The four monomers play a synergistic role in the polyketone copolymer and jointly improve the glass transition temperature of the polymer. When the polymer contains structures of formula I and formula II at the same time, the configuration of the polyketone copolymer is changed. The change in configuration causes changes in the physical and chemical properties of the polyketone copolymer, thereby significantly improving the glass transition temperature of the polyketone copolymer. The glass transition temperature is ≥276°C, which is greater than the glass transition temperature when the structure of formula I or the structure of formula II exists alone. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is an image showing the change in Tg in Test 1 with increasing molar content of 1,4-bis(4-fluorobenzoyl)benzene.

[0020] Figure 2 This is a glass transition temperature image of the polyketone copolymer prepared in Example 7 of the present invention. DETAILED DESCRIPTION

[0021] In order to facilitate understanding by those skilled in the art, the present invention is further described below in conjunction with specific embodiments.

[0022] A method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure comprises the following steps: (1) In an inert atmosphere and in the presence of a catalyst, 2-benzimidazolone, phthalazinone biphenol and a dihalogenated monomer containing a benzene ring are polymerized in an organic solvent to obtain a polymer precursor; (2) The polymer precursor obtained in step (1) is purified and then treated to obtain a polyketone copolymer; In step (1), the total amount of 2-benzimidazolidinone and phthalazinone biphenol and the amount of the dihalogenated monomer containing a benzene ring are in a ratio of 1-1.06:1-1.06, the amount of the phthalazinone biphenol and 2-benzimidazolidinone is preferably 0.01-0.99:0.01-0.99, and further preferably, the amount of the phthalazinone biphenol and 2-benzimidazolidinone is 0.05-0.65:035-0.95, and the total amount of the phthalazinone biphenol and 2-benzimidazolidinone and the amount of the catalyst are preferably 1:1.04-1.12.

[0023] The present invention uses special monomers 2-benzimidazolidinone and phthalazinone biphenol as nucleophilic monomers in the polymerization reaction. 2-benzimidazolidinone contains nitrogen-hydrogen reaction sites, and phthalazinone biphenol contains nitrogen-hydrogen and hydroxyl reaction sites, which can react with dihalogenated compounds containing benzene rings, introduce nitrogen elements through dehydration condensation, increase the content of nitrogen elements in the polymer, and form a coupling product similar to carbon-carbon bonding, which enhances the solubility of the polymer while increasing the glass transition temperature of the polymer. Specifically, the content of carbon-nitrogen bonds in the polyketone copolymer is increased by 2-benzimidazolidinone and phthalazinone biphenol, and the bond energy of the carbon-nitrogen bond is much greater than the bond energy of the ether bond, so that the glass transition temperature and thermal stability of the polyketone copolymer are improved. The nitrogen in phthalazinone biphenol is embedded in the cyclic structure of the benzene ring, which can also effectively increase the thermal stability of the polymer. At the same time, the twisted, non-coplanar phthalazinone biphenol structure can avoid the characteristics of the polyketone copolymer forming a linear configuration, increase the gap between the polymer main chains, facilitate the penetration of small organic solvent molecules, improve the solubility of the polyketone copolymer, avoid the problem of increased structural rigidity due to carbon-nitrogen bonding and decreased overall polymer solubility due to structural rigidity, and make the polymer easy to process. The amorphous polyketone copolymer of the present invention is suitable for manufacturing high-temperature molding systems and other manufactured items through injection molding, extrusion, compression molding, blow molding, thermoforming, rotational molding, coating and additive manufacturing.

[0024] Specifically, in step (1) of the present invention, the inert atmosphere is preferably nitrogen or argon atmosphere, the catalyst is preferably anhydrous sodium carbonate or anhydrous potassium carbonate, and the organic solvent is preferably any one or a combination of several of diphenyl sulfone, cumene hydroperoxide, N,N-dimethylformamide, cyclopentane, and N-cyclohexylpyrrolidone. The organic solvent is preferably dehydrated, and the dehydration process of each organic solvent is a conventional technical means in the art and will not be described in detail here.

[0025] The dihalogenated monomer containing a benzene ring in the present invention is preferably Formula I, and / or Formula II, wherein Y is chlorine or fluorine, X is chlorine or fluorine, the halogens in Formula I and Formula II may be the same or different, and the monomer containing the structure of Formula I in the present invention is 1,4-bis(4-fluorobenzoyl)benzene or 1,4-bis(4-chlorobenzoyl)benzene, and the monomer containing the structure of Formula II is 4,4'-difluorobenzophenone or 4,4'-dichlorobenzophenone.

[0026] When the dihalogenated monomer containing a benzene ring is a monomer containing a structure of formula II, the molar ratio of diazinone biphenol and 2-benzimidazolinone is 0.05-0.6:0.4-0.95, and the copolymer prepared thereby has an intrinsic solution viscosity greater than 0.1dL / g and a glass transition temperature greater than 270°C.

[0027] When the dihalogenated monomer containing a benzene ring is a monomer containing a structure of formula I and a monomer containing a structure of formula II, the molar ratio of the monomer containing a structure of formula I to the monomer containing a structure of formula II is preferably 7-60:40-93. More preferably, the molar ratio of the monomer containing a structure of formula I to the monomer containing a structure of formula II is 15:85.

[0028] When the dihalogenated monomer containing a benzene ring of the present invention is a monomer containing a structure of formula I and a monomer containing a structure of formula II, 2-benzimidazolidinone and diazinone biphenol are subjected to dehydration condensation with the monomer containing a structure of formula I and the monomer containing a structure of formula II, respectively, to form a polyketone copolymer containing four monomers. The four monomers play a synergistic role in the polymer. When the monomer containing a structure of formula I and the monomer containing a structure of formula II coexist, the configuration of the polyketone copolymer when the structure of formula I or the structure of formula II exists alone is changed, thereby causing changes in its physical and chemical properties, and significantly improving the glass transition temperature of the polyketone copolymer to above 276°C.

[0029] The preparation of the polymer precursor in step (1) of the present invention specifically includes the following steps: S1: at 140-200°C, 2-benzimidazolinone and phthalazinone-biphenol react with a catalyst to generate salts respectively, the reaction time is 1-2 hours, and the reaction system is dehydrated until the water content of the reaction system is ≤1000ppm; S2: raising the temperature of step S1 to 180-280° C., and performing a prepolymerization reaction between the salt of step S1 and the dihalogenated monomer containing a benzene ring to obtain a prepolymer, and the reaction time is 0.5-6 hours; S3: At 220-320° C., the prepolymer of step S2 is further polymerized to obtain a polymer precursor, and the reaction time is 2-8 hours.

[0030] When 2-benzimidazolidinone, phthalazinone biphenol and the catalyst undergo salt-forming reaction, the temperature is lower than 140°C, the reaction rate is slow, resulting in increased reaction time and extended production cycle. When the temperature is higher than 200°C, the reaction monomer is easily oxidized, which is not conducive to the subsequent polymerization reaction. In the present invention, the salt-forming reaction is preferably carried out at 140-200°C, and more preferably at 160-180°C. In the present invention, the dihalogenated monomer containing a benzene ring can be added before the salt-forming reaction starts, or after the salt-forming reaction ends.

[0031] In step S1, water in the reaction system is taken away by adding a water-carrying agent or vacuum distillation before the start of the salt-forming reaction, thereby promoting the polymerization reaction and reducing side reactions. The water-carrying agent is preferably toluene or xylene, and the volume ratio of the water-carrying agent to the organic solvent is 0.4-0.6:1. Before the reaction starts, the water-carrying agent is added to the reaction system together with the reaction raw materials, and the water-carrying agent and water are azeotropically dehydrated. Specifically, the temperature of the reaction system during dehydration is preferably 160-280°C, and the dehydration time is 1-2h. Further preferably, the temperature of the reaction system during dehydration is 180-200°C.

[0032] The prepolymerization reaction in the present invention mainly occurs in step S2. During the reaction of 2-benzimidazolinone and phthalazinone biphenol with the catalyst in step S1, a small amount of monomers will undergo prepolymerization reaction. Step S3 of the present invention adopts gradient heating, and the heating rate is preferably 1-5°C / min.

[0033] When the dihalogenated monomer containing a benzene ring is a monomer containing a structure of formula I or a monomer containing a structure of formula II, the prepolymerization temperature is preferably 180-220°C, and the reaction time is 0.5-6h; the polymerization temperature is preferably 220-280°C, and the reaction time is 2-6h.

[0034] When the dihalogenated monomer containing a benzene ring is a mixture of a monomer containing a structure of formula I and a monomer containing a structure of formula II, the prepolymerization temperature is preferably 200-280°C, and the reaction time is 2-6 hours; the polymerization temperature is preferably 280-320°C, and the reaction time is 2-8 hours. In a preferred embodiment of the present invention, the prepolymerization temperature is 220°C, and the reaction time is 3 hours.

[0035] As a preferred embodiment of the present invention, when the dihalogenated monomer containing a benzene ring is a mixture of a monomer containing a structure of formula I and a monomer containing a structure of formula II, in step S3, the prepolymer is first reacted at 280°C for 2h, then heated to 300°C for reaction for 2h, and finally reacted at 320°C for 4h, wherein the heating rate is 1°C / min. By increasing the reaction temperature by three heating reactions, the polymerization of the polymerized monomers is more complete, and the quality of the product can be improved.

[0036] The post-purification treatment in step (2) includes the following steps: T1: adding the mixture after the reaction in step S3 into a dispersant and dispersing it so that the polymer particles are ≤1 mm; T2: At 60-100°C, filter the dispersed material in step T1, then wash it several times with a 3%-50% by mass phosphoric acid aqueous solution and pure water and filter it, transfer the filtered solid to a container, add pure water and stir it under reflux overnight for hot filtration, and then dry it.

[0037] Specifically, after the polymerization reaction of step S3 in the present invention is completed, the reaction system is first poured into pure water and mixed for 3-5 minutes, and then the reaction system is poured into a wall breaking machine equipped with a dispersant for wall breaking and dispersion after filtration, and the polymer is dispersed into a solid with a particle size of ≤1mm. Specifically, the mass ratio of the dispersed material to the volume ratio of the dispersant is preferably 1g:4-10mL, and further preferably, the mass ratio of the dispersed material to the volume ratio of the dispersant is 1g:6mL, and the dispersant is preferably water, methanol or ethanol.

[0038] In step T2 of the present invention, the polymer is washed with phosphoric acid aqueous solution and pure water for multiple times, and finally stirred overnight under reflux to reduce the content of metal ions in the polymer and improve the purity of the polyketone copolymer. In step T2, the material is dried at a temperature of 120-160° C. for a drying time of 8-24 hours.

[0039] In order to improve the stability of the material, the present invention adds an antioxidant before the salt-forming reaction in step (1), adds a stabilizer after the polymerization reaction, or adds a stabilizer after the purification treatment in step (2). The antioxidant is preferably phosphorous acid or a phosphite, and more preferably any one of potassium dihydrogen phosphite, sodium dihydrogen phosphite, potassium monohydrogen phosphite, sodium monohydrogen phosphite, potassium phosphite, and sodium phosphite. The stabilizer is preferably an organic phosphorus-containing stabilizer, and more preferably an organic phosphorus-containing stabilizer with a heat resistance higher than 350°C, such as tris(nonylphenyl)phosphite, tris(2,4-di-tert-butylphenyl)phosphite, and one of pentaerythritol dioctadecylphosphite. The amount of the antioxidant or stabilizer to the total amount of 2-benzimidazolinone and phthalazinone diphenol is preferably 0.005%-0.3%:1.

[0040] The present invention also provides a high-performance polyketone copolymer containing a phthalazinone structure synthesized by the above preparation method, wherein the polyketone copolymer comprises repeating units shown in Formula 1 and Formula 2: Formula 1 is , and / or, ; Formula 2 is , and / or, ; The total number of repeating units shown in Formula 1 is a, and the total number of repeating units shown in Formula 2 is b, where a and b are both positive integers, 1≤a≤5000, and 1≤b≤5000. DETAILED DESCRIPTION Example 1

[0041] Raw material ratio: weigh 5.615 g (23.58 mmol) of phthalazinone biphenol, 1.830 g (12.7 mmol) of 2-benzimidazolinone, 11.812 g (36.64 mmol) of 1,4-bis(4-fluorobenzoyl)benzene, 5.215 g (37.73 mmol) of anhydrous potassium carbonate, 4.4 mg (0.036 mmol) of potassium dihydrogen phosphite, 50 mL of solvent cumene hydroperoxide (purity 99.9%), and 20 mL of dehydrating agent xylene (purity 99.9%); Experimental steps: (1) Argon was introduced into a 250 mL four-necked round-bottom flask. Under slow stirring, phthalazinone biphenol, 2-benzimidazolinone, 1,4-bis(4-fluorobenzoyl)benzene, anhydrous potassium carbonate, potassium dihydrogen phosphite, isopropylbenzene hydroperoxide and xylene were added according to the raw material ratio. Then the temperature of the reaction system was raised to 140°C and maintained for 0.5 h. phthalazinone biphenol, 2-benzimidazolinone and anhydrous potassium carbonate reacted to form potassium salt. During this process, the reaction mixture was an orange liquid. The temperature was further raised to 165°C and the salt-forming reaction was continued for 1.5 h. The water produced by the reaction refluxed into the water separator together with xylene. The xylene on the upper layer of the water separator refluxed into the four-necked round-bottom flask, and the water on the lower layer of the water separator was directly discharged. The water content of the reaction system was less than 5 ppm, and the reaction mixture was an opaque low-viscosity solution with a gray color. Prepolymerization: The reaction system was heated to 180°C for prepolymerization for 4 hours. The remaining water and xylene were distilled into the water separator and the reaction mixture became viscous. Polymerization reaction: the reaction temperature was raised to 220°C at a heating rate of 3°C / min, and the reaction was carried out for 3 hours to obtain a polymer precursor. The mixture after the reaction was poured into 200 mL of pure water, mixed for 3 minutes, and then filtered to obtain the mixture; (2) Dispersion: Add the filtered mixture and pure water into a grinder at a mass ratio of the filtered mixture to pure water of 1 g:4 mL, crush the mixture into solid powders less than 0.5 mm and then filter; Washing: add the filtered solid powder and 300 mL of 10% H3PO4 to a four-necked flask at 80°C, with the stirrer speed at 250 rpm, stir for 3 min and filter, then mix and stir with 300 mL of pure water for 1 h, then filter, repeat the washing process of adding H3PO4 and pure water twice, transfer the filtered solid and 150 mL of pure water to a 250 mL flask, stir under reflux overnight and perform hot filtration; Drying: The washed solid powder was dried at 140°C for 12 h to obtain the final product.

[0042] A high-performance polyketone copolymer containing a phthalazinone structure was obtained by using the experimental steps of this example. Example 2

[0043] Raw material ratio: phthalazinone biphenol 5.86g (24.6mmol), 2-benzimidazolone 1.77g (13.24mmol), 1,4-bis(4-fluorobenzoyl)benzene 8.458g (15.29mmol), 4,4'-difluorobenzophenone 5.641g (22.93mol), anhydrous potassium carbonate 5.754g (41.63mmol), organic solvent diphenyl sulfone (purity 99.9%) 50mL, dehydrating agent toluene (purity 99.9%) 24mL; Experimental steps: (1) Nitrogen is introduced into a 250 mL four-necked round-bottom flask. Under slow stirring, add phthalazinone biphenol, 2-benzimidazolone, 1,4-bis(4-fluorobenzoyl)benzene, 4,4'-difluorobenzophenone, anhydrous potassium carbonate, diphenyl sulfone and toluene according to the raw material ratio. The temperature of the reaction system is heated to 180°C. phthalazinone biphenol, 2-benzimidazolone and anhydrous potassium carbonate react for 1 hour to form a dipotassium salt. The reaction system is an orange slurry. The water and toluene produced by the reaction are azeotropically refluxed into the water separator. The toluene in the upper layer of the water separator refluxes into the four-necked round-bottom flask. The water in the lower layer of the water separator is directly discharged. The water content of the reaction system is less than 5ppm. Prepolymerization: The reaction system was heated to 220°C for prepolymerization. The reaction time was 3 hours. The residual toluene and water in the reaction system were distilled into the water separator. The reaction system was a viscous orange slurry. Polymerization reaction: at a heating rate of 1°C / min, the reaction temperature was first raised to 280°C for 2 h, then raised to 300°C for 2 h, and finally raised to 320°C for 4 h to obtain a polymer precursor, and then the reaction mixture was poured into 250 mL of pure water and mixed for 5 min, and then filtered; (2) Dispersion: Add the filtered mixture and methanol into a pulverizer at a mass ratio of the filtered mixture to methanol of 1 g:6 mL, crush the mixture into solid powders less than 1.0 mm, and then filter; Washing: Control the temperature at 60°C, add the filtered solid powder and 60 mL of 50% H3PO4 to a four-necked flask, set the stirrer speed at 350 rpm, stir for 5 min and filter, then mix and stir with 350 mL of pure water for 1 h, then filter, repeat the washing process of adding H3PO4 and pure water three times, transfer the filtered solid and 120 mL of pure water to a 250 mL flask, stir under reflux overnight and perform hot filtration; Drying: The washed solid powder was dried at 120°C for 24 h to obtain the final product.

[0044] A high-performance polyketone copolymer containing a phthalazinone structure was obtained by using the experimental steps of this example. Example 3

[0045] A high-performance polyketone copolymer was synthesized according to the steps and conditions of Example 2, except that the total amount of 1,4-bis(4-fluorobenzoyl)benzene and 4,4'-difluorobenzophenone in this example remained unchanged, and the molar ratio of 1,4-bis(4-fluorobenzoyl)benzene to 4,4'-difluorobenzophenone was 60:40. Example 4

[0046] A high-performance polyketone copolymer was synthesized according to the steps and conditions of Example 2, except that the total amount of 1,4-bis(4-fluorobenzoyl)benzene and 4,4'-difluorobenzophenone in this example remained unchanged, and the molar ratio of 1,4-bis(4-fluorobenzoyl)benzene to 4,4'-difluorobenzophenone was 15:85. Example 5

[0047] A high-performance polyketone copolymer was synthesized according to the steps and conditions of Example 2, except that the total amount of 1,4-bis(4-fluorobenzoyl)benzene and 4,4'-difluorobenzophenone in this example remained unchanged, and the molar ratio of 1,4-bis(4-fluorobenzoyl)benzene to 4,4'-difluorobenzophenone was 7:93. Example 6

[0048] Raw material ratio: weigh 5.594 g (23.48 mmol) of phthalazinone biphenol, 5.2 g (23.48 mmol) of 2-benzimidazolone, 10.35 g (47.44 mmol) of 4,4'-difluorobenzophenone, 7.14 g (51.66 mmol) of anhydrous sodium carbonate, 60 mL of solvent N-cyclohexyl-2-pyrrolidone (purity 99.9%), and 30 mL of water-carrying agent xylene (purity 99.9%) respectively; Experimental steps: (1) Argon was introduced into a 250 mL four-necked round-bottom flask. Under slow stirring, phthalazinone diphenol, 2-benzimidazolone, anhydrous sodium carbonate, N-cyclohexyl-2-pyrrolidone and 20 mL of xylene were added according to the raw material ratio. Then the temperature of the reaction system was raised to 155°C and maintained for 0.5 h, and then raised to 175°C and maintained for 1 h. phthalazinone diphenol, 2-benzimidazolone and anhydrous sodium carbonate reacted to form sodium salt, and xylene and water were distilled into the water separator. The reaction temperature was lowered to 155°C, and 4,4'-difluorobenzophenone and 10 mL of xylene were added. The reaction mixture was heated to 175°C and maintained for 0.5 h. The remaining xylene and water in the system were distilled into the water separator. Prepolymerization: The reaction system was heated to 210°C for prepolymerization. The reaction was continued for 1 hour. The remaining xylene and water in the system were distilled into the water separator. The reaction mixture was a viscous brown slurry. Polymerization reaction: the reaction temperature was raised to 280°C at a heating rate of 5°C / min, and the reaction was carried out for 6 hours to obtain a polymer precursor. The mixture after the reaction was poured into 200 mL of pure water, mixed for 3 minutes, and then filtered to obtain the mixture; (2) Dispersion: Add the filtered mixture and pure water into a grinder at a mass ratio of the filtered mixture to pure water of 1 g:5 mL, crush the mixture into solid powders less than 0.5 mm and then filter; Washing: at 100°C, add the filtered solid powder and 350 mL of 3% H3PO4 into a four-necked flask, with the stirrer speed at 300 rpm, stir for 3 min and filter, then mix and stir with 350 mL of pure water for 2 h, then filter, repeat the washing process of adding H3PO4 and pure water twice, transfer the filtered solid and 150 mL of pure water into a 250 mL flask, stir under reflux overnight and perform hot filtration; Drying: The washed solid powder was dried at 120° C. for 24 h to obtain a polyketone copolymer.

[0049] A high-performance polyketone copolymer containing a phthalazinone structure was obtained by using the experimental steps of this example. Example 7

[0050] Raw material ratio: weigh 1.63 g (6.84 mmol) of phthalazinone biphenol, 5.20 g (38.77 mmol) of 2-benzimidazolone, 10.051 g (46.06 mmol) of 4,4'-difluorobenzophenone, 6.93 g (50.17 mmol) of anhydrous sodium carbonate, 60 mL of solvent N-cyclohexyl-2-pyrrolidone (purity 99.9%), and 30 mL of water-carrying xylene (purity 99.9%) respectively; Experimental steps: (1) Nitrogen was introduced into a 250 mL four-necked round-bottom flask. Under slow stirring, phthalazinone biphenol, 2-benzimidazolone, anhydrous sodium carbonate, N-cyclohexyl-2-pyrrolidone and 20 mL of xylene were added according to the raw material ratio. Then the temperature of the reaction system was raised to 155°C and maintained for 0.5 h, and then raised to 175°C and maintained for 1 h. phthalazinone biphenol, 2-benzimidazolone and anhydrous sodium carbonate reacted to form sodium salt. The xylene on the upper layer of the water separator refluxed into the four-necked round-bottom flask, and the water on the lower layer of the water separator was directly discharged. The temperature was cooled to 155°C, and then 4,4'-difluorobenzophenone and 10 mL of xylene were added. Then the temperature was heated to 175°C and maintained for 0.5 h. The remaining xylene and water in the system were distilled into the water separator. Prepolymerization: The reaction system was heated to 220°C for prepolymerization for 0.5 h. The reaction mixture was a viscous brown slurry. Polymerization reaction: the reaction temperature was raised to 280°C at a heating rate of 5°C / min, and the reaction was carried out for 4 hours to obtain a polymer precursor. The mixture after the reaction was poured into 300 mL of pure water, mixed for 3 minutes, and then filtered to obtain the mixture; (2) Dispersion: Add the filtered mixture and pure water into a grinder at a mass ratio of the filtered mixture to pure water of 1 g:5 mL, crush the mixture into solid powders less than 0.5 mm and then filter; Washing: at 100°C, add the filtered solid powder and 350 mL of 3% H3PO4 into a four-necked flask, with the stirrer speed at 300 rpm, stir for 3 min and filter, then mix and stir with 350 mL of pure water for 2 h, then filter, repeat the washing process of adding H3PO4 and pure water twice, transfer the filtered solid and 150 mL of pure water into a 250 mL flask, stir under reflux overnight and perform hot filtration; Drying: The washed solid powder was dried at 120° C. for 24 h to obtain a polyketone copolymer.

[0051] A high-performance polyketone copolymer containing a phthalazinone structure was obtained by using the experimental steps of this embodiment. The glass transition temperature of the polyketone copolymer prepared in this embodiment is 292°C. Figure 2 shown. Example 8

[0052] Raw material ratio: weigh 5.454 g (22.9 mmol) of phthalazinone biphenol, 3.3 g (22.9 mmol) of 2-benzimidazolone, 14.836 g (46.03 mmol) of 1,4-bis(4-fluorobenzoyl)benzene, 6.963 g (50.38 mmol) of anhydrous potassium carbonate, and 80 mL of solvent N-cyclohexylpyrrolidone (purity 99.9%); Experimental steps: (1) Nitrogen was introduced into a 250 mL four-necked round-bottom flask. Under slow stirring, phthalazinone biphenol, 2-benzimidazolone, 1,4-bis(4-fluorobenzoyl)benzene, anhydrous potassium carbonate, and N-cyclohexylpyrrolidone were added according to the raw material ratio. Then the temperature of the reaction system was raised to 140°C, and phthalazinone biphenol, 2-benzimidazolone and anhydrous potassium carbonate were reacted for 1.5 hours to generate potassium salt. The temperature of the reaction system was raised to 160°C, and vacuum distillation was performed for 1 hour to remove the water produced by the reaction. The water content of the reaction system was less than 5 ppm. Prepolymerization: The reaction system was heated to 220°C for prepolymerization for 2 hours. The reaction mixture was a viscous gray slurry. Polymerization reaction: the reaction temperature was raised to 280°C at a heating rate of 5°C / min, and the reaction was carried out for 6 hours to obtain a polymer precursor. The mixture after the reaction was poured into 250 mL of pure water, mixed for 4 minutes, and then filtered to obtain the mixture; (2) Dispersion: Add the filtered mixture and ethanol into a grinder at a mass ratio of the filtered mixture to ethanol of 1 g:6 mL, crush the mixture into solid powders less than 1 mm, and then filter; Washing: at 100°C, add the filtered solid powder and 300 mL of 10% H3PO4 to a four-necked flask, with the stirrer speed at 300 rpm, stir for 8 min and filter, then mix and stir with 300 mL of pure water for 1.5 h, then filter, repeat the washing process of adding H3PO4 and pure water twice, transfer the filtered solid and 150 mL of pure water to a 250 mL flask, stir under reflux overnight and perform hot filtration; Drying: The washed solid powder was dried at 140°C for 12 h to obtain the final product.

[0053] A high-performance polyketone copolymer containing a phthalazinone structure was obtained by using the experimental steps of this example. Example 9

[0054] Raw material ratio: weigh 3.82 g (16.03 mmol) of phthalazinone biphenol, 3.466 g (24.05 mmol) of 2-benzimidazolone, 14.35 g (40.4 mmol) of 1,4-bis(4-chlorobenzoyl)benzene, 6.204 g (44.89 mmol) of anhydrous potassium carbonate, and 50 mL of solvent N-cyclohexylpyrrolidone (purity: 99.9%); Experimental steps: (1) Nitrogen was introduced into a 250 mL four-necked round-bottom flask. Under slow stirring, phthalazinone biphenol, 2-benzimidazolone, 1,4-bis(4-chlorobenzoyl)benzene, anhydrous potassium carbonate, and N-cyclohexylpyrrolidone were added according to the raw material ratio. Then the temperature of the reaction system was raised to 140°C, and phthalazinone biphenol, 2-benzimidazolone and anhydrous potassium carbonate were reacted for 1.5 hours to generate potassium salt. The temperature of the reaction system was raised to 160°C, and the water produced by the reaction was removed by vacuum distillation for 1 hour. The water content of the reaction system was less than 5 ppm. Prepolymerization: The reaction system was heated to 200°C for prepolymerization for 0.5 h. The reaction mixture was a viscous gray slurry. Polymerization reaction: the reaction temperature was raised to 250°C at a heating rate of 1°C / min, and the reaction was carried out for 5 hours to obtain a polymer precursor. The reaction mixture was then poured into 200 mL of pure water, mixed for 4 minutes, and then filtered to obtain the mixture; (2) Dispersion: Add the filtered mixture and ethanol into a grinder at a mass ratio of the filtered mixture to ethanol of 1 g:6 mL, crush the mixture into solid powders less than 1 mm, and then filter; Washing: at 100°C, add the filtered solid powder and 300 mL of 10% H3PO4 to a four-necked flask, with the stirrer speed at 300 rpm, stir for 8 min and filter, then mix and stir with 300 mL of pure water for 1.5 h, then filter, repeat the washing process of adding H3PO4 and pure water twice, transfer the filtered solid and 150 mL of pure water to a 250 mL flask, stir under reflux overnight and perform hot filtration; Drying: The washed solid powder was dried at 140°C for 12 h to obtain the final product.

[0055] A high-performance polyketone copolymer containing a phthalazinone structure was obtained by using the experimental steps of this example. Example 10

[0056] Raw material ratio: weigh 96 mg (0.4 mmol) of phthalazinone biphenol, 5.83 g (39.68 mmol) of 2-benzimidazolone, 8.25 g (37.81 mmol) of 4,4'-difluorobenzophenone, 33 mg (0.046 mmol) of pentaerythritol dioctadecyl diphosphite, 6.2 g (44.89 mmol) of anhydrous sodium carbonate, 65 mL of solvent N,N-dimethylformamide (purity 99.9%), and 22 mL of water-carrying xylene (purity 99.9%); Experimental steps: (1) Nitrogen was introduced into a 250 mL four-necked round-bottom flask. Under slow stirring, phthalazinone biphenol, 2-benzimidazolone, 4,4'-difluorobenzophenone, anhydrous sodium carbonate, N,N-dimethylformamide and xylene were added according to the raw material ratio. Then the temperature of the reaction system was raised to 200°C. phthalazinone biphenol, 2-benzimidazolone and anhydrous sodium carbonate were reacted for 1 hour to form sodium salt. The xylene in the upper layer of the water separator was refluxed into the four-necked round-bottom flask. The water in the lower layer of the water separator was directly discharged. The water content of the reaction system was less than 5 ppm. Prepolymerization: The reaction system was heated to 280°C for prepolymerization for 6 hours. The remaining xylene and water in the system were distilled into the water separator. The reaction mixture was a viscous brown slurry. Polymerization reaction: the reaction temperature was raised to 320°C at a heating rate of 5°C / min, and the reaction was carried out for 2 hours to obtain a polymer precursor. The reaction mixture was then poured into 200 mL of pure water, mixed for 3 minutes, and then filtered to obtain the mixture; (2) Dispersion: Add the filtered mixture and pure water into a grinder at a mass ratio of the filtered mixture to pure water of 1 g:5 mL, crush the mixture into solid powders less than 0.5 mm and then filter; Washing: at 100°C, add the filtered solid powder and 350 mL of 3% H3PO4 into a four-necked flask, with the stirrer speed at 300 rpm, stir for 3 min and filter, then mix and stir with 350 mL of pure water for 2 h, then filter, repeat the washing process of adding H3PO4 and pure water twice, transfer the filtered solid and 150 mL of pure water into a 250 mL flask, stir under reflux overnight and perform hot filtration; Drying: The washed solid powder is dried at 120° C. for 24 hours to obtain a polyketone copolymer, and pentaerythritol dioctadecyl diphosphite is added to the polyketone copolymer and mixed uniformly to obtain a final product.

[0057] A high-performance polyketone copolymer material containing a phthalazinone structure was obtained by using the experimental steps of this embodiment. Embodiment 11

[0058] Raw material ratio: weigh 9.456g (39.68mmol) of phthalazinone biphenol, 58mg (0.4mmol) of 2-benzimidazolinone, 10.662g (42.48mmol) of 4,4'-dichlorobenzophenone, 33mg (0.046mmol) of pentaerythritol dioctadecyl diphosphite, 5.757g (41.68mmol) of anhydrous sodium carbonate, 50mL of solvent N,N-dimethylformamide (purity of 99.9%), and 22mL of water-carrying agent xylene (purity of 99.9%) respectively; Experimental steps: (1) Nitrogen was introduced into a 250 mL four-necked round-bottom flask. Under slow stirring, phthalazinone biphenol, 2-benzimidazolone, 4,4'-dichlorobenzophenone, anhydrous sodium carbonate, N,N-dimethylformamide and xylene were added according to the raw material ratio. Then the temperature of the reaction system was raised to 200°C. phthalazinone biphenol, 2-benzimidazolone and anhydrous sodium carbonate were reacted for 1 hour to form sodium salt. The xylene in the upper layer of the water separator was refluxed into the four-necked round-bottom flask. The water in the lower layer of the water separator was directly discharged. The water content of the reaction system was less than 5 ppm. Prepolymerization: The reaction system was heated to 200°C for prepolymerization for 2 hours. The remaining xylene and water in the system were distilled into the water separator. The reaction mixture was a viscous brown slurry. Polymerization reaction: the reaction temperature was raised to 280°C at a heating rate of 5°C / min, and the reaction was carried out for 8 hours to obtain a polymer precursor. The reaction mixture was then poured into 200 mL of pure water, mixed for 3 minutes, and then filtered to obtain the mixture; (2) Dispersion: Add the filtered mixture and pure water into a grinder at a mass ratio of the filtered mixture to pure water of 1 g:5 mL, crush the mixture into solid powders less than 0.5 mm and then filter; Washing: at 100°C, add the filtered solid powder and 350 mL of 3% H3PO4 into a four-necked flask, with the stirrer speed at 300 rpm, stir for 3 min and filter, then mix and stir with 350 mL of pure water for 2 h and filter again, repeat the washing process of adding H3PO4 and pure water twice, transfer the filtered solid and 150 mL of pure water into a 250 mL flask, stir under reflux overnight and perform hot filtration; Drying: The washed solid powder is dried at 120° C. for 24 hours to obtain a polyketone copolymer, and pentaerythritol dioctadecyl diphosphite is added to the polyketone copolymer and mixed uniformly to obtain a final product.

[0059] A high-performance polyketone copolymer material containing a phthalazinone structure was obtained by using the experimental steps of this embodiment.

[0060] Test 1: The polymerization was carried out according to the steps and reaction conditions of Example 2 to obtain a polyketone copolymer, except that the molar content of 1,4-bis(4-fluorobenzoyl)benzene in the dihalogenated monomer containing a benzene ring in the reaction system was changed, and the molar content of 1,4-bis(4-fluorobenzoyl)benzene was gradually increased from 0 to 100%.

[0061] Effect test of the polyketone copolymer of the present invention The polyketone copolymers prepared in Examples 1-11 were subjected to differential scanning calorimetry (DSC), intrinsic viscosity, metal ion content test and UL-94 test, respectively, to obtain the data in Table 1.

[0062] The high-performance polyketone copolymer prepared in Test 1 was subjected to differential scanning calorimetry (DSC) to obtain the glass transition temperature of the polymer, and the variation of Tg with increasing molar content of 1,4-bis(4-fluorobenzoyl)benzene was plotted. Figure 1 .

[0063] The DSC test conditions were as follows: from 100 to 450 °C, the temperature was increased at a rate of 20 °C / min; Intrinsic viscosity: measured using a 200-size Cannon-Fenske capillary at 30°C in N-methylpyrrolidone at 0.5 wt / vol%, expressed in dL / g; Metal ion content test: add 300 mL of pure water to the prepared polyketone copolymer, stir for 5 minutes and filter, measure the ionic conductivity in the filtrate, and calculate the metal ion content according to the ionic conductivity calculation formula; Flame retardancy is tested according to UL-94 fire rating test standard.

[0064] Table 1 Polyketone copolymer performance test table

[0065] It can be concluded from Table 1 that the polyketone copolymer prepared by the synthesis method of the present invention has a higher glass transition temperature, which is above 253°C, higher than the glass transition temperature of ordinary polyketone copolymers. Figure 1 It can be seen that when the polymer contains both Formula I and Formula II, the Tg of the prepared polyketone copolymer is greater than or equal to 276°C, which is higher than the glass transition temperature when Formula I or Formula II exists alone, indicating that the diazonium ketone biphenol, 2-benzimidazolidinone, the monomer containing the structure of Formula I and the monomer containing the structure of Formula II in the present invention play a synergistic role in the polyketone copolymer and jointly improve the glass transition temperature of the polyketone copolymer.

[0066] As the proportion of the formula II structure in the total amount of the polyketone copolymer increases, the glass transition temperature of the polyketone copolymer gradually increases. When the amount ratio of the monomer containing the formula I structure to the monomer containing the formula II structure is 15:85, the glass transition temperature of the polyketone copolymer reaches the highest, which is 290°C. This may be because the molecular weight of the monomer containing the formula II structure is less than the molecular weight of the monomer containing the formula I structure, thereby reducing the number average molecular weight of the polymer and indirectly increasing the nitrogen-carbon bond content in the polymer. The UL-94 fire rating is the highest level V0, and the polyketone copolymer has good heat resistance and stability. The residual metal ions in the polyketone copolymer are less than or equal to 69ppm, indicating that the amount of metal ions is effectively reduced by acid washing and pure water washing, and the purity of the polyketone copolymer is improved, and the application scenarios are broader.

[0067] In summary, in the present invention, phthalazinone biphenol and 2-benzimidazolinone are used as nucleophilic monomers to react with dihalogenated monomers containing a benzene ring to obtain a polyketone copolymer with a Tg of ≥253°C. The polyketone copolymer prepared by the present invention can be applied to high temperature environments and has a long service life; phthalazinone biphenol and 2-benzimidazolinone provide carbon-nitrogen bonds for the polyketone copolymer, thereby improving the thermal stability of the material, and the non-coplanar structure of phthalazinone biphenol alleviates the problem of reduced material solubility due to the increase in carbon-nitrogen bonds.

[0068] It should be understood that the purpose of these embodiments is only to illustrate the present invention and is not intended to limit the protection scope of the present invention. In addition, it should also be understood that after reading the technical content of the present invention, those skilled in the art can make various changes, modifications and / or variations to the present invention, and all of these equivalent forms also fall within the protection scope defined by the claims attached to this application.

Claims

1. A method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure, characterized in that: The following steps are involved: (1) In an inert atmosphere and in the presence of a catalyst, 2-benzimidazolone, phthalazinone biphenol and a dihalogenated monomer containing a benzene ring are polymerized in an organic solvent to obtain a polymer precursor; (2) The polymer precursor obtained in step (1) is purified and then treated to obtain a polyketone copolymer; The total amount of the 2-benzimidazolidinone and phthalazinone biphenol and the amount of the dihalogenated monomer containing a benzene ring are in a ratio of 1-1.06:1-1.06, and the amount of the phthalazinone biphenol and 2-benzimidazolidinone is in a ratio of 0.01-0.99:0.01-0.99; In step (1), the total amount of 2-benzimidazolidinone and phthalazinone biphenol to the amount of catalyst is 1:1.04-1.

12.

2. The method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure according to claim 1, characterized in that: The dihalogenated monomer containing a benzene ring in step (1) is Formula I, and / or Formula II; Wherein, Y is chlorine or fluorine, X is chlorine or fluorine, and Y and X are the same or different.

3. The method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure according to claim 2, characterized in that: When the dihalogenated monomer containing a benzene ring in step (1) is a monomer containing a structure of formula I and a monomer containing a structure of formula II, the molar ratio of the monomer containing a structure of formula I to the monomer containing a structure of formula II is 7-60:40-93.

4. The method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure according to claim 3, characterized in that: The molar ratio of the monomer containing the structure of formula I to the monomer containing the structure of formula II is 15:

85.

5. The method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure according to claim 2, characterized in that: When the dihalogenated monomer containing a benzene ring is a monomer containing a structure of formula II, the molar ratio of the diazonium ketone biphenol to 2-benzimidazolinone is 0.05-0.6:0.4-0.

95.

6. The method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure according to claim 1, characterized in that: In step (1), the catalyst is selected from anhydrous sodium carbonate or anhydrous potassium carbonate; The organic solvent is selected from any one of diphenyl sulfone, cumene hydroperoxide, N,N-dimethylformamide, sulfolane, and N-cyclohexylpyrrolidone, or a combination of several of them.

7. The method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure according to claim 2, characterized in that: The preparation of the polymer precursor in step (1) comprises the following steps: S1: at 140-200°C, 2-benzimidazolinone and phthalazinone-biphenol react with a catalyst to generate salts respectively, the reaction time is 1-2 hours, and the reaction system is dehydrated until the water content of the reaction system is ≤1000ppm; S2: raising the temperature to 180-280° C., and performing a prepolymerization reaction between the salt and the dihalogenated monomer containing a benzene ring to obtain a prepolymer, and the reaction time is 0.5-6 hours; S3: polymerizing the prepolymer in step S2 to obtain a polymer precursor at 220-320°C, with a reaction time of 2-8h; Step S3 adopts gradient heating, and the heating rate is 1-5°C / min.

8. The method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure according to claim 7, characterized in that: When the dihalogenated monomer containing a benzene ring is a monomer containing a structure of formula I and a monomer containing a structure of formula II, the prepolymer in step S3 is reacted at 280° C. for 2 hours, then heated to 300° C. for 2 hours, and finally reacted at 320° C. for 4 hours, and the heating rate is 1° C. / min.

9. The method for synthesizing a high-performance polyketone copolymer containing a phthalazinone structure according to claim 7, characterized in that: The post-purification treatment in step (2) comprises the following steps: T1: adding the mixture after the reaction in step S3 into a dispersant and dispersing it so that the polymer particles are ≤1 mm; T2: at 60-100° C., the dispersed material in step T1 is washed multiple times with a 3%-50% by mass phosphoric acid aqueous solution and pure water, and then dried to obtain a polyketone copolymer.

10. A high-performance polyketone copolymer containing a phthalazinone structure obtained by the synthesis method according to any one of claims 1 to 9, characterized in that: The polyketone copolymer comprises repeating units shown in Formula 1 and Formula 2: Formula 1 is , and / or, ; Formula 2 is , and / or, ; The total number of repeating units shown in Formula 1 is a, and the total number of repeating units shown in Formula 2 is b, wherein a and b are both positive integers, 1≤a≤5000, and 1≤b≤5000.

Citation Information

Patent Citations

  • A polyaryletherketone and its preparation method

    CN103450478B

  • Polymers and copolymers containing 2H-benzimidazol-2-one moieties

    US8609801B2

  • Method for preparing polyetheretherketone with phthalazone pyridine structure

    CN107501490A

  • Novel crystallizable and dissolvable polyetheretherketone ketone ketone resin containing diazanaphthalene terphenyl structure and preparation method thereof

    CN110563905A

  • High temperature polyketone copolymers

    CN115551835A